An optimal energy management strategy for a stand-alone PV/wind/battery hybrid energy system - Zebraoui, Otmane; Bouzi, Mostafa; Nasiri, Badr (Institute of Advanced Engineering and Science, 2025)
This paper presents an optimization study of a stand-alone hybrid energy system that includes a photovoltaic energy generator, a wind energy generator, and lithium-ion storage batteries. In the proposed system architecture, solar, and wind sources are utilized as the primary power generators, while batteries serve as a secondary storage to ensure system autonomy across varying weather conditions. The aim is to improve system performance through an optimal energy management strategy that addresses operational constraints and electrical load needs while managing energy flow between sources and controlling the storage system. To manage energy flow between sources and load, an intelligent approach using a hierarchical algorithm is proposed to configure the optimal operating mode based on the power from both sources, load power, and battery state of charge. Additionally, a controller is developed to manage battery operating modes, ensuring state of charge (SOC) limits and maintaining a constant direct current (DC) bus voltage. Under varying operating conditions, the simulation results show the efficiency of the proposed management strategy in maintaining the power balance between supply and demand, providing a stable and continuous power supply, and keeping the batteries SOC within its limits and the DC bus voltage at its reference value.